Neutronic Evaluation of Using a Thorium Sulfate Solution in an Aqueous Homogeneous Reactor - D. Milian; L. Hernández; D. Lorenzo; C. Brayner; D. Pérez; A. Gámez (PPIKSN-BATAN, 2022)
Radioisotope 99Mo is one of the most essential radioisotopes in nuclear medicine. Its production in an Aqueous Homogeneous Reactor (AHR) could be potentially advantageous compared to the traditional technology, based on target irradiation in a heterogeneous reactor. An AHR conceptual design using low-enriched uranium for the production of 99Mo has been studied in depth. So far, the possibility of replacing uranium with a non-uranium fuel, specifically a mixture of 232Th and 233U, has not been evaluated in the conceptual design. Therefore, the studies conducted in this article aim to evaluate the neutronic behavior of the AHR conceptual design using thorium sulfate solution. Here, the 232Th-233U composition to guarantee ten years of operation without refueling, conversion ratio, medical isotopes production levels, and reactor kinetic parameters were evaluated, using the computational code MCNP6. It was obtained that 14 % 233U enrichment guarantees the reactor operation for ten years without refueling. The conversion ratio was calculated at 0.14. The calculated 99Mo production in the AHR conceptual design resulted in 24.4 % higher with uranium fuel than with thorium fuel.